Strategic Marketing Issues in Emerging Markets (Springer Singapore, 2018)
This book presents a collection of articles addressing a range of marketing strategies unique to emerging economies. It describes the component of strategic and tactical marketing, including the marketing mix, segments and targeting, product and market orientation, employing the Internet and social media, penetration and loyalty strategies and innovation, and other strategy issues in the marketing context. In addition, the book focuses on creating, communicating, and delivering customer value to emerging market consumers through diverse marketing strategies, processes, and programs in the context of emerging markets' dynamics, consumer diversity, and competitors. Bringing together contributors from industry and academia to explore key marketing issues prevalent in India and other emerging economies, the book offers a unique and insightful read for a global audience. "This book, edited by Dr. Atanu Adhikari, offers important analytical and managerial insights into consumer behavior, firm strategy, market dynamics and marketing instruments (price, promotion, distribution and product). While marketing and management disciplines have developed useful empirical generalizations, the context is critical. This book does exactly that -- place the generalized results in the context of emerging markets and India. Accordingly, this is a valuable resource for scholars and practitioners." -- Dr. Gurumurthy Kalyanaram, Professor, City University of New York, USA and Tata Institute of Social Sciences, Mumbai, India; US Editor, International Journal of Learning and Change; and President, MIT South Asian Alumni Association "This book is a must-read for anyone interested in marketing to less-developed countries. While the focus of the chapters is on India, the lessons learned can be generally applied. The 34 chapters represent comprehensive coverage of nearly every topic related to marketing with many examples. Any manager interested in doing business in emerging markets, Professors who want a better knowledge of these markets, or students who want an excellent reference should acquire this book." -- Dr. Russell S. Winer, William Joyce Professor of Marketing, Stern School of Business, New York University, USA.